Effect of erythromycin and modulating effect of CeO2 NPs on the toxicity exerted by the antibiotic on the microalgae Chlamydomonas reinhardtii and Phaeodactylum tricornutum. (November 2018) - Sendra, Marta; Moreno-Garrido, Ignacio; Blasco, Julián; Araújo, Cristiano V.M.
Abstract: Erythromycin is an antibiotic employed in the treatment of infections caused by Gram positive microorganisms and the increasing use has made it a contaminant of emerging concern in aqueous ecosystems. Cerium oxide nanoparticles (CeO2 NPs), which are known to have catalytic and antioxidant properties, have also become contaminants of emerging concern. Due to the high reactivity of CeO2 NPs, they can interact with erythromycin magnifying their effects or on the other hand, considering the redox potential of CeO2 NPs, it can alleviate the toxicity of erythromycin. The present study was carried out to assess the toxicity of both single compounds as well as mixed on Chlamydomonas reinhardtii and Phaeodactylum tricornutum (freshwater and marine microalgae respectively) employed as target species in ecotoxicological tests. Mechanisms of oxidative damage and those harmful to the photosynthetic apparatus were studied in order to know the toxic mechanisms of erythromycin and the joint effects with CeO2 NPs. Results showed that erythromycin inhibited the microalgae population growth and effective quantum yield of PSII (E.Q.Y.) in both microalgae. However, the freshwater microalgae Chlamydomonas reinhardtii was more sensitive than the marine diatom Phaeodactylum tricornutum . Responses related to the photosynthetic apparatus such as E.Q.Y. was affected by the exposure to erythromycin of both microalgae, as chloroplasts are target organelle for this antibiotic. Mixed experiments (CeO2 NPs + erythromycin) showed the protective role of CeO2 NPs in both microalgae preventing erythromycin toxicity in toxicological responses such as the growth of the microalgae population and E.Q.Y. Graphical abstract: Image 1 Highlights: Erythromycin effects modulated by CeO2 NPs were tested at environmental concentrations. C. reinhardtii was more sensitive to erythromycin than P. tricornutum . The protective role of single treatments with CeO2 NPs was observed in both microalgae. The toxicity of erythromycin was more pronounced in the photosynthetic apparatus. CeO2 NPs alleviated the effects of erythromycin on growth and effective quantum yield.